Pelatihan Akuntansi Koperasi bagi Koperasi Simpan Pinjam di Kabupaten Subang - Mulyati, Sri; Nursely, Dinda; Aliya, Esta Rahma; Kartika, Intan; Nuroktaviani, Ria; Patonah, Silpia Fitri; Agisna, Yuli (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service program aims to improve the understanding and accounting skills of savings and loan cooperative managers in Subang Regency, with a focus on increasing transparency and accountability in financial management. The program implementation method includes identifying needs and problems, designing training programs, and implementing and evaluating them. The training is structured through a combination of lectures, group discussions, case studies, and hands-on practice sessions. The results of the program showed a significant increase in participants' understanding and skills related to cooperative accounting, as well as positive changes in financial management practices. Pre-test and post-test evaluations showed a significant increase in scores, namely from a pre-test average of 52.46 and a post-test average of 74.22. Participant satisfaction surveys showed positive feedback on the content and teaching methods. This program contributed to improving the financial performance of cooperatives and increasing member confidence, as well as providing positive implications for local economic development in Subang Regency.